Seismic Performance of Concentrically Steel Braced Frames with Eccentric Gusset Plates - Amin Ghannadiasl (Iranian Society of Structrual Engineering (ISSE), 2019)
Different types of the lateral-load resisting systems to deal with lateral forces entering the building are used in buildings such as the concentrically braced frames (CBFs). The application of the concentrically braced frames is welcomed due to its lateral stiffness and other benefits. In accordance with the regulations, the brace axis should meet at the intersection point of the column centroid and the beam centroid axes. In many cases, the eccentric gusset plates at the connection of the brace and the beam are observed in the concentrically braced frames. Therefore, in this paper, the effect of the eccentricities at the connection of braces on the behavior of the CBFs including the in-plane and out-plane eccentricities of the gusset plate by finite element method is investigated in order to determine the optimal performance of the structure when the if the failure of the regulations observes. Hence, 11 models are used to determine the margin of confidence for non-observance of the rules of the regulations in the frames with Eccentric Gusset Plates using the Abacus software. The results show that the effect of the in-plane eccentricities is far more unfavorable than the out-plane eccentricities and there is little margin of confidence for non-observance of the rules of the regulations.